The Effect of The Number of Coffee Purchases On The Income of Drying Workers In CV. Oro Coffee Gayo In Central Aceh District - Eliyin; Ilma Fitri; Mahyudin Ariga (International Journal of Science, Technology & Management, 2022)
This research was conducted at CV. Oro Kopi Gayo, Central Aceh Regency, this research was conducted in February 2016. The location determination was determined intentionally by considering that CV. Oro Kopi Gayo is one of the industrial companies engaged in coffee processing and coffee export. The data analysis method used simple linear regression analysis. Based on the results of the partial analysis, the value of tcount = 5.121 > ttable = 2.228 with a significant value obtained 0.000 or <0.05 (5%) then H0 is rejected and Hadi accepts. This shows that the independent variable (number of random purchases) has a partially significant effect on the dependent variable (drying labor acceptance). The average number of random purchases of coffee is 289,552 Kg\Year with the average number of drying workers receiving Rp.33,684,0984, From the results of this study indicate that the higher the number of random coffee purchases, the higher the labor acceptance. drying. So that it can be concluded that the proposed simple linear regression equation model Y=q+bX is acceptable.